Bacteremia caused by an Acinetobacter junii strain harboring class 1 integron and diverse DNA mobile elements - Traglia, German Matias (2014)
INTRODUCTION: Infections caused by Acinetobacter junii are rarely reported. However, some outbreaks of septicemia in neonates and pediatric oncology patients, as well as meningitis, peritonitis, and ocular infection have been described. Since it is highly infrequent to find the molecular characterization of A. junii strains in literature, in this study we described the molecular characterization of A. junii isolates recovered from blood samples of a renal transplant patient. METHODOLOGY: The case was defined as a catheter-related bacteremia caused by A. junii. The patient responded favorably after catheter removal and treatment with ciprofloxacin. RESULTS AND CONCLUSION: The complete molecular characterization of the isolate showed that it harbored a class 1 integron and diverse DNA mobile elements. This explains its genomic plasticity for acquiring antimicrobial resistance determinants and for adapting to a nosocomial niche.